2022
DOI: 10.1002/tal.1977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ASCE 41‐17 performance‐based provisions on optimally designed steel moment frames

Abstract: In this study, the ASCE 41-17 nonlinear static procedure for steel moment-resisting frames is evaluated using a three-phase constraint handling procedure. For the first time, advanced performance measures of ASCE 41-17 are quantified during the optimization process by constructing concentrated plasticity models of the standard.Covariance matrix adaptation in evolution strategies (CMA-ES) is used to obtain optimal designs for three-and nine-story illustrative examples. Active and inactive constraints are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hosseini Lavassani et al (2022) investigated optimal linguistic design variables of fuzzy logic controllers to explain the behavior of a fifteen-story structure under pulse-type earthquake records. Ebadijalal and Shahrouzi (2022) studied the optimal structural weight with respect to collapse margin ratio. The authors concluded that there is no direct strong relationship between seismic safety and optimal weight of steel momentresisting frames.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hosseini Lavassani et al (2022) investigated optimal linguistic design variables of fuzzy logic controllers to explain the behavior of a fifteen-story structure under pulse-type earthquake records. Ebadijalal and Shahrouzi (2022) studied the optimal structural weight with respect to collapse margin ratio. The authors concluded that there is no direct strong relationship between seismic safety and optimal weight of steel momentresisting frames.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between structural optimization and seismic evaluation is another intriguing research topic. Ebadijalal and Shahrouzi (2022) demonstrated that metaheuristic algorithms can generate sample structures for evaluation purposes. Ghasemiazar and Gholizadeh (2022) evaluated the seismic safety of several chevron-braced frames that were topologically optimized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations